The Reality of Strategic Planning in the General Administrations of Specialized Banks Case Study: General Administration of Agricultural Bank Branches, Eastern Region (Al-Mukhtar Journal of Economic Sciences, 2022)
The study aimed to identify the reality of strategic planning among employees of the General Administration of Agricultural Bank branches in the eastern region. The problem of the study was crystallized in the question: What is the reality of the strategic planning of the General Administration of the branches of the Agricultural Bank in the eastern region? The researcher used the descriptive approach and extracted the arithmetic averages, standard deviations, and the relative importance of all dimensions of strategic planning, where the researcher relied on questionnaires as a tool for study and statistical analysis spss to analyze the data descriptively and inferentially. The number of agricultural workers in the eastern region is (50), and the sample amounted to 44. 44 questionnaires were retrieved, of which three were excluded. The study concluded with the most important results, the most important of which is that the bank does not have a clear, specific and written vision for future aspirations that serves its goals and the goals of society, and its vision does not aim for growth and a promising future outlook, and the bank's mission does not depend on participation in preparing an integrated vision and a comprehensive long-term view for all parties. The study recommended the need for senior management to support the concept of strategic planning through the development of administrative methods used and the preparation of the vision, mission and strategic objectives in light of the results of the analysis of the internal and external environment of the bank with the need to involve the internal bank community when reformulating or updating the vision and mission of the organization and that all those responsible for achieving them participate in the formulation of the bank's goals, and the goals must be quantitatively expressed in order to facilitate measurement and the extent of progress made in achieving them.
Keywords: Strategic Planning; General Management; Agricultural Bank